Surveying the youth-to-senior transition landscape in Major League Soccer: a new frontier - Mannix, P.; Roberts, S. J.; Enroght, K.; Littlewood, M. (Science and Medicine in Football, 2024)
Purpose: The aim of this study was to survey Major League Soccer stakeholders` attitudes and perspectives on the youth-to-senior transition with a particular interest in the league`s evolving club structures, specifically the reserve team and youth academy entities. The survey assessed various stakeholders` views on clubs` organisational aims and structure, the capabilities of club entities to prepare players for the first team, and the transition process to the first team within MLS. Methods: A total of 80 participants working in various `player operation` roles for MLS clubs in the United States and Canada voluntarily completed the online survey. Results: The predominant aim for both reserve teams and academies in MLS is to develop players for the first team. The organisational structure and governance of reserve teams are varied across the league, but an overarching feature is their function as a development team. When players are transitioning, communication between staff may or may not be clear and effective. Finally, for players within an MLS club`s talent pathway, a variety of support strategies are made available during the transition into the first team, but psychological support in particular may be limited or unavailable. Conclusion: Similar to European soccer, the aim of MLS reserve teams and youth academies is to develop first team players for the club. However, while players are transitioning into the first team, communication may or may not be clear and effective, and psychological support may be absent, which may impair player development initiatives.